2020
DOI: 10.1111/ggi.13987
|View full text |Cite
|
Sign up to set email alerts
|

Mediation and moderated mediation in the relationships among income condition, depression, cognition and residence among older adults in China

Abstract: Aim: A better income condition has always been associated with better cognition; however, studies that have demonstrated the pathway of this relationship are limited. We aim to evaluate the mediation effect of depression in this association, and whether this mediation is moderated by the place of residence. Methods: We conducted a face-to-face study, including 3230 older adults aged >60 years in Xiamen, China, in 2016. The income condition of participants was categorized into three groups: income less than exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The association between income status and mental health has been reported in the literature. Existing studies reveal that, income status obtained by individuals has a significant influence on their health outcomes, including their mental and physical health, particularly in the case of elderly adults (31)(32)(33)(34). Further, findings from (35) reveal that, the likelihood of depressions, mental disorders, and anxiety decrease when economic status or income level rise.…”
Section: Theoretical Foundation and Research Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between income status and mental health has been reported in the literature. Existing studies reveal that, income status obtained by individuals has a significant influence on their health outcomes, including their mental and physical health, particularly in the case of elderly adults (31)(32)(33)(34). Further, findings from (35) reveal that, the likelihood of depressions, mental disorders, and anxiety decrease when economic status or income level rise.…”
Section: Theoretical Foundation and Research Hypothesesmentioning
confidence: 99%
“…Findings from the hypothesized relationships demonstrate that satisfaction of belongingness and respect, the improvement of income, and the exertion of human capital also have positive direct influence on the mental health of the elderly who participate in the local non-agricultural employment. The plausible explanation is that, the elderly adults who are employed or participate in self-employment are able to improve their income levels, ease any financial burden, and improve their life satiation, well-being, and mental stress, which are all indicators of a sound mental health (31)(32)(33)(34). Again the continuous utilization of the physical strength, human capital and professional skills of the elderly contribute significantly to their mental health.…”
Section: Mechanism Analysismentioning
confidence: 99%
“…Furthermore, the type of residency (rural or urban) significantly predicted cognitive functioning in all the selected countries. A study by Yuan et al 2020 observed that individuals residing in an urban area have better cognition [ 36 ] due to perceived better income conditions than their counterparts in rural residences. This study observed that most respondents in China, Ghana, and India lived in rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Sundström et al 2016 and Feng et al 2014 revealed that unmarried adults have a high propensity of suffering from cognitive impairments leading to dementia than married adults [ 34 , 35 ]. Previous research has also observed that rural dwellers tend to have a significantly higher prevalence of cognitive limitations than their counterparts in urban residences [ 36 , 37 ]. Research on the association between sex and cognitive functioning has produced mixed results.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, targeting extra risk factors related to SB among the elderly population with depression could significantly reduce suicides. Similar to the case in other age groups, the elderly commit suicide because of the combined effect of psychic, mental, physical, social, and cultural concerns, suggesting a high heterogeneity in late‐life suicide 6,7 . For example, impulsivity is considered to be the SB endophenotype, but many elderly people who attempt suicide have shown low impulsivity.…”
Section: Introductionmentioning
confidence: 89%